Intake of vitamin D and calcium, sun exposure, and risk of breast cancer subtypes among black women. Issue 2 (11th December 2019) - Qin, Bo; Xu, Baichen; Ji, Nan; Yao, Song; Pawlish, Karen; Llanos, Adana A M; Lin, Yong; Demissie, Kitaw; Ambrosone, Christine B; Hong, Chi-Chen; Bandera, Elisa V
ABSTRACT: Background: The randomized placebo-controlled Vitamin D and Omega-3 Trial suggested a possible benefit of vitamin D on cancer incidence among black individuals. However, data are limited regarding the impact of vitamin D on breast cancer subtypes among African-American/black women, who tend to develop more aggressive forms of breast cancer. Objectives: We hypothesize that more vitamin D exposure (through diet, supplements, and sunlight) and higher intake of calcium are associated with decreased risk of estrogen receptor (ER)+ and ER− breast cancer, and of triple-negative breast cancer (TNBC) among black women. Methods: This study was conducted among 1724 black cases and 1233 controls in the Women's Circle of Health Study (WCHS) and WCHS2. Polytomous logistic regressions were used to estimate ORs and 95% CIs of ER+ and ER− breast cancer; logistic regressions were used for TNBC. The ORs from each study were pooled using an inverse-variance-weighted random-effects model. Results: Dietary vitamin D and calcium intake were not associated with risk of breast cancer subtypes in the pooled analysis. For supplemental vitamin D, we observed possible inverse associations between intake of ≤800 IU/d (compared with nonuse) and risk of several subtypes, with effects that appeared strongest for TNBC (OR: 0.58; 95% CI: 0.35, 0.94); no association was found for >800 IU/d. More daylight hours spent outdoors in a year was associated with lower risk of ER+, ER−, and TNBC (e.g., highest compared with lowest quartile: TNBC OR: 0.53; 95% CI: 0.31, 0.91; P -trend = 0.02). Conclusions: Moderate supplemental vitamin D intake was associated with decreased risk of TNBC, and increased sun exposure was associated with reduced risk of ER+, ER−, and TNBC among black women.